2006
DOI: 10.1002/pen.20625
|View full text |Cite
|
Sign up to set email alerts
|

Recycling poly(ethylene terephtalate) wastes: Properties of poly(ethylene terephtalate)/polycarbonate blends and the effect of a transesterification catalyst

Abstract: The article addresses the issue of recycling of poly(ethylene terephtalate) (PET) by melt blending with polycarbonate (PC). PET/PC blends containing various amounts of the immiscible polymers were prepared in a twin-screw extruder. Selected compositions were also prepared in the presence of an Sn-based catalyst to assess the influence of transesterification during melt mixing. The degree of miscibility in the blends was studied using differential scanning calorimetry, scanning electron microscopy, and mechanic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 22 publications
1
25
0
1
Order By: Relevance
“…PC90 blend has the finest dispersed phase compared with PC80 or PC70 that have a less uniform dispersion with a higher number average particle size. Significantly, the number average particle size of dispersed phases that are mentioned here are in the same range that has been cited by other works for blends containing equal or more than 10% by weight of PET [27][28][29][30].…”
Section: Sem Analysissupporting
confidence: 82%
See 1 more Smart Citation
“…PC90 blend has the finest dispersed phase compared with PC80 or PC70 that have a less uniform dispersion with a higher number average particle size. Significantly, the number average particle size of dispersed phases that are mentioned here are in the same range that has been cited by other works for blends containing equal or more than 10% by weight of PET [27][28][29][30].…”
Section: Sem Analysissupporting
confidence: 82%
“…There is a shift in curves to make space between them and so the maximum and width peak of the peaks appear clearer components especially in the presence of catalysts. This copolymer may reduce the mobility of the PET chains on the crystal surface because of the constraints from the high T g PC domains and the copolymer chains will also act as defects during chain folding [27]. In addition, the reduced particle size and the well distribution of these particles could play an important rule in the T cc shifting.…”
Section: Sem Analysismentioning
confidence: 99%
“…A co-continuous morphology with small droplets can be found only in 50% PC as shown in Figure 2(b). Mbarek et al have also reported that a cocontinuous morphology is only found in a 50/50 blend composition of PET/PC [22].…”
Section: Phase Morphology Studies Of Rpet/pc Blendsmentioning
confidence: 98%
“…Para a preparação das blendas, a primeira etapa foi a pré-mistura dos dois polímeros nas quantidades de PET/PA de 1500/0 (PET), 1125/375 (PA25), 750/750 (PA50), 375/1125 (PA75) e 0/1500 (PA) em gramas juntamente com 1,5 mL do catalisador 2-etilexanoato de estanho (II) para cada amostra, medidos em uma pipeta volumétrica. O catalisador tem como função auxiliar na compatibilidade das blendas durante a etapa seguinte de extrusão, por meio da catálise de trans-reações entre o PET e a PA [13] .…”
Section: Introductionunclassified